Reviews on Corrugated Diaphragms in Miniature Fiber-Optic Pressure Sensors - Honglin Li; Hui Deng; Guangqi Zheng; Mingguang Shan; Zhi Zhong; Bin Liu (Applied Sciences, 2019)
Corrugated diaphragms (CDs) have been widely used in many fields because of their higher pressure sensitivity and wider linear range compared to flat diaphragms (FDs) in the same circumstances. Especially in the application of miniature fiber-optic pressure sensors, the introduction of the corrugated structure gives the sensor high sensitivity, large dynamic range, good linearity, small hysteresis, good stability, and so on. Research on CD-based miniature fiber-optic pressure sensors has gradually attracted more attention in recent years. In this paper, the principles of operation of a miniature fiber-optic pressure sensor are briefly introduced, then the mechanical properties of FD and CD, as well as their influences on the performance of the sensor, are analyzed in detail. The application status of CDs in miniature fiber-optic pressure sensors is reviewed, and our conclusions and the prospects for the application of CDs in miniature fiber-optic pressure sensors are given finally.